2015
DOI: 10.4102/curationis.v38i1.1172
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices toward breast cancer screening in a rural South African community

Abstract: ObjectivesThe study assessed the knowledge, attitudes and breast cancer screening practices amongst women aged 30–65 years residing in a rural South African community.MethodA quantitative, descriptive cross-sectional design was used and a systematic sampling technique was employed to select 150 participants. The questionnaire was pretested for validity and consistency. Ethical considerations were adhered to in protecting the rights of participants. Thereafter, data were collected and analysed descriptively usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 17 publications
4
41
0
3
Order By: Relevance
“…The findings found in this study are supported by other studies that have also shown promising results in increasing women's knowledge about breast cancer, risk factors and diagnostic methods for early detection from the use of educational strategies (13)(14)(15) . It should be noted that different educational strategies were proposed in these studies, such as the development of focus groups, the application of an educational manual, a community intervention program, and others.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings found in this study are supported by other studies that have also shown promising results in increasing women's knowledge about breast cancer, risk factors and diagnostic methods for early detection from the use of educational strategies (13)(14)(15) . It should be noted that different educational strategies were proposed in these studies, such as the development of focus groups, the application of an educational manual, a community intervention program, and others.…”
Section: Discussionsupporting
confidence: 88%
“…The information about the magnitude of the risk is important, so that it is aware of this, revealing that the term breast cancer is typically associated with public campaigns that may be effective, increasing the awareness of the population, but sometimes they are not effective in motivate women to seek preventive and disease control treatments (14) , which was not observed in this study, since most of the participants presented an adequate attitude regarding the early detection of breast cancer.…”
Section: Discussionmentioning
confidence: 71%
“…6 Various studies have recognised the need for breast cancer health education programmes. [11][12][13][14][15] However, it is necessary to address barriers to breast cancer awareness and early detection in the context of the local population's presiding social and cultural beliefs. 9,10,16,17 Health education interventions therefore need to be culturally and linguistically tailored, while still portraying breast cancer as a treatable disease.…”
mentioning
confidence: 99%
“…Significant knowledge insufficiencies can have a detrimental effect on the education of women on screening and early detection practices [34]. In the current study, knowledge about BSE was found to be the major predictor for practice of BSE, after confounding factors being controlled for.…”
Section: Discussionmentioning
confidence: 47%